Analisis Kesalahan Siswa Dalam Menyelesaikan Soal Pemecahan Masalah Berdasarkan Kriteria Polya - Fitria Nova; Yulia Haryono; Alfi Yunita (STKIP PGRI Sumatera Barat, 2021)
This study aims to determine the forms of errors made by students based on Polya’s criteria and to determine the factors that cause students to make these mistakes. This type of research is a qualitative research that is analyzed using a descriptive approach in the form of a case study rearch. The subjects in this study were students of class X IPA 4 which consisted of 28 students. The analytical method used in this research is descriptive-qualitative analysis. The results showed that there were 91.7% of students errors in understanding the problem, errors in formulating problems were 34.5% of students, carried out errors in implementing plans were 24.5% of students and errors when checking back answer 38.1% of students. Factors causing these errors: (1) students are less interested in learning mathematics, (2) students are less talented in mathematics, (3) students who have difficulty working on problems and (4) how to teach teachers in providing explanations about mathematics lessons.